Analisis Campur Kode pada Lirik Lagu Jaran Goyang Dipopulerkan oleh Nella Kharisma - Devi Ardiyanti; Ririn Setyorini (SAP (Susunan Artikel Pendidikan), 2018)
A song lyric is a person's expression of something that he has seen, heard or experienced. In expressing his experience, poet or song writer play with words and languages to  create attractive and unique lyrics or poems. This qualitative research uses a qualitative descriptive method. The research is related to interpretation and description of data. The song lyric Jaran Goyang created by Andi Mbendol serves as the main object of this research. The research uses a purposive sampling technique and applies triangulation of data and theory. Data are analyzed using descriptive analysis technique, in which data are collected employing 2 techniques,namely reading and writing techniques. The purpose of this research is to know what type of code mixing contained in Jaran Goyang song lyrics, what kind of languages used, and what messages to be delivered. The result of this research shows there is code mixing in the song lyrics, namely inner mixing code of Javanese and outer mixing code of English.